Correlations between Severity of Disease with Anxiety Levels in Glaucoma Patients - Maulida Zahra; Arief Wildan; Riski Prihatningtias; Fifin Luthfia Rahmi (Diponegoro International Medical Journal, 2020)
Background: Glaucoma is a group of diseases consisting of optic neuropathy characterized by damage to the retinal nerve fibers and narrowing of the visual field accompanied by increased intraocular pressure as a risk factor. Vision loss in glaucoma patients is considered as a separate stressor. Besides that, decrease visual function can also cause a person to lose his job and loss of social functions. This can trigger anxiety to depression.Objective: To analyze the correlations between the severity of disease with anxiety levels in glaucoma patients.Methods: This was an observational analytic study with a cross-sectional design. Subjects were taken by consecutive sampling with inclution criterias were patients with moderate or severe glaucoma, able to follow the interview process and 30-80 years old. The exclusion criteria of this study were patients who was taking anti-anxiety, antidepressant, or antipsychotic drugs and having other serious / chronic disease such as heart disease, diabetes, or hypertension. Anxiety level was assessed based on the Taylor Manifest Anxiety Scale (TMAS) questionnaire. Analysis of the data using the Spearman Correlation test.Results: Sixty five glaucoma patients who underwent treatment in out patients department dr. Kariadi hospital were involved in this study.  A significant correlation was obtained between the severity of glaucoma and the level of anxiety (p = 0.004). Strong statistical correlation between variables included in the weak category (0.357). The highest anxiety level in glaucoma patients was moderate anxiety level (64.6%), followed by mild anxiety level (23.1%) and severe anxiety level (12.3%).Conclusion: There were significant correlation between the severity of the disease and the level of anxiety in glaucoma patients.